Ultra-fine high-performance microcrystalline cellulose product and preparation method therefor
The high-shearing mechanical process enhances fine crystal cellulose to ultra-fine particle sizes and high densities, addressing limitations in existing technologies and improving its performance and applicability in pharmaceuticals and food industries.
Patent Information
- Application Number
- JP2024174156
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-04-13
- Filing Date
- 2024-10-03
- Publication Date
- 2025-01-31
AI Technical Summary
Existing methods for producing fine crystal cellulose struggle to achieve ultra-fine particle sizes and high densities, limiting their applicability and performance in industries such as pharmaceuticals and food, particularly in processes requiring good fluidity and compression.
A high-shearing mechanical process using a high-shear force device, such as a screw extruder, is employed to reduce particle diameter and increase density of fine crystal cellulose to 1-25 μm and 0.5-0.8 g/ml, respectively, by controlling the torque between 20-150 N·m and adjusting solid content during processing.
The resulting ultra-fine, high-density cellulose products exhibit improved fluidity and compression characteristics, expanding their application in pharmaceuticals and food industries, including uses as binding agents, flavor masking, and encapsulation, with enhanced performance in tabletting and molding processes.
Smart Images

Figure 2025016394000001_ABST
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to the field of microcrystalline cellulose, and in particular to an ultrafine, high performance microcrystalline cellulose product and a method for its preparation.
[0002] [Background technology] Microcrystalline cellulose is a fluid fine powder made by hydrolyzing natural cellulose with dilute acid to the levelling off degree of polymerization (LODP). It is white or nearly white in color, tasteless and odorless. The ultimate degree of polymerization (LODP) is usually 100-350. It is insoluble in water, dilute acids, organic solvents, and grease. It partially dissolves and swells in dilute alkaline aqueous solutions. Microcrystalline cellulose has stable properties even under conditions of high temperature, high humidity, and strong light irradiation, and is widely used in various industries such as medicine, food, daily chemicals, and light industry.
[0003] Microcrystalline cellulose, as a pharmaceutical auxiliary material, is widely applied in the medical industry. In the pharmaceutical industry, it is mainly used as an adhesive, disintegrant and filler, mainly used in the tableting process. It can be used in wet granulation, dry granulation and direct tableting. It has excellent pressure resistance and plays the role of disintegration and lubrication. It is an important pharmaceutical auxiliary material. Due to its unique porous structure, microcrystalline cellulose can also exert the sustained release effect of medicines. Microcrystalline cellulose can be used as dietary fiber, which is an important functional food base material in the food industry. It is an ideal food additive and can be used as a fat substitute.
[0004] Microcrystalline cellulose is available in many varieties, including PH 101 (average particle size 40-60 μm, loose density 0.26-0.32 g / mL), PH 102 (average particle size 70-100 μm, loose density 0.28-0.33 g / mL), PH 103 (average particle size 45-75 μm, loose density 0.26-0.34 g / mL), and PH 112 (average particle size 90-140 μm, loose density 0.28-0.37 g / mL). There are also special types of microcrystalline cellulose products with high density or small particle size, such as PH301 (average particle size 40-60 μm, loose density 0.34-0.45 g / ml), PH302 (average particle size 90-140 μm, loose density 0.35-0.50 g / ml), and PH105 (average particle size 20-40 μm, loose density 0.2-0.3 g / ml).
[0005] The table below is taken from the product manual of ASAHI in Japan and shows the product parameters listed on the packaging of common microcrystalline cellulose products available on the market.
[0006] [Table 1]
[0007] Microcrystalline cellulose has different application characteristics for products with different particle sizes and densities. In general, the smaller the particle size of microcrystalline cellulose, the more advantageous it is for uniform mixing with other ingredients such as pharmaceuticals, and it is suitable for mixing with materials with small particle sizes or materials with low active ingredient content to improve the uniformity of the content. In addition, conventional microcrystalline cellulose with small particle sizes has the unique advantage that the smaller the particle size, the higher the strength performance of the tablet. However, microcrystalline cellulose tends to have lower fluidity as the particle size becomes smaller, making it unsuitable for formulation such as direct compression, and its application to medicines and foods is greatly limited.
[0008] Small particle size microcrystalline cellulose products have been conventionally produced by dry grinding, sieving, and ball milling, especially in the presence of grinding aids. Chinese invention patent CN101481424B discloses that microcrystalline cellulose is decomposed by 60Co-γ irradiation, ultrafine-powdered, and mechanically ground and / or chemically decomposed to obtain ultrafine-powdered crystalline cellulose with a particle size of 10 μm or less. However, the density of the microcrystalline cellulose products produced by these methods is not very high. Commercially available microcrystalline cellulose products with small particle size generally have an average particle size D50 of about 15-30 μm and a moderate density of 0.2-0.3 g / ml. Therefore, there is a problem that the smaller the particle size, the worse the flowability. This greatly limits the application in industry.
[0009] China invention patent CN109666078A discloses a method for preparing microcrystalline cellulose by acid hydrolysis after high shear mechanical pretreatment. In the pretreatment process, the high shear mechanical force cuts the fibers, improves the accessibility of the acid solution to the cellulose, increases the penetration rate of the acid solution into the cellulose, and increases the acid hydrolysis rate of the acid solution into the cellulose amorphous region, which can reduce the use of chemicals or reaction time. The density of the microcrystalline cellulose prepared by this method is not improved, and the average particle size of the microcrystalline cellulose product is still above 38.7 μm.
[0010] China invention patent CN110229239A discloses microcrystalline cellulose with high loose density and its preparation method. The filter cake obtained by acid hydrolysis is kneaded in a kneader and spray-dried to obtain a microcrystalline cellulose product with a loose density of 0.6-0.65g / cm3. However, the particle size of this microcrystalline cellulose product is also large, with the average particle size D50 reaching 45-50μm.
[0011] Chinese invention patents CN103726378A, CN103526624A and CN1671743A also disclose methods for preparing microcrystalline cellulose. However, the particle size or loose density of the microcrystalline cellulose products prepared by these methods are not within the scope of the present invention. For example, the particle size is more than 25 μm or the loose density is much lower than 0.5 g / ml.
[0012] Summary of the Invention The present invention provides a microcrystalline cellulose product with ultrafine particle size and extremely high density and a method for producing the same, in order to overcome the shortcomings of the prior art microcrystalline cellulose products. The microcrystalline cellulose product of the present invention has better performance and wider application fields.
[0013] The technical scheme of the present invention is as follows:
[0014] The present invention provides microcrystalline cellulose particles, characterized in that the microcrystalline cellulose particles have an average particle size D50 of 1 to 25 μm and a loose density of 0.5 to 0.8 g / ml. Preferably, the microcrystalline cellulose particles have an average particle size D50 of 1 to 25 μm and a loose density of 0.52 to 0.75 g / ml. More preferably, the microcrystalline cellulose particles have an average particle size D50 of 10 to 20 μm and a loose density of 0.55 to 0.75 g / ml.
[0015] Preferably, the microcrystalline cellulose particles are obtained from normal microcrystalline cellulose by high shear mechanical action, and the solid content of the normal microcrystalline cellulose is 15% to 60% when subjected to high shear mechanical action. More preferably, the solid content of the normal microcrystalline cellulose is 30% to 50% when subjected to high shear mechanical action.
[0016] Preferably, the high shear mechanical action is performed using a high shear device with a torque of more than 20 N·m. More preferably, the high shear mechanical action is performed using a high shear device with a torque of more than 50 N·m. The high shear device is preferably a screw extruder having high strength and high shear force, such as a screw extruder, a screw kneader, or a screw extrusion kneader. The high shear device may be continuous or intermittent, and may be divided into multi-stage, multi-time, and repeated processing.
[0017] Another object of the present invention is to provide a method for preparing the above-mentioned microcrystalline cellulose particles, which comprises a step of applying high shear mechanical action to normal microcrystalline cellulose via a high shear mechanical action, characterized in that the solid content of the normal microcrystalline cellulose is 15% to 60% in the high shear mechanical action. More preferably, the solid content concentration of the normal microcrystalline cellulose in the high shear mechanical action is 30% to 50%. The high shear mechanical action is performed using a high shear force device having a torque of 20 N·m or more. More preferably, the high shear mechanical action is performed using a high shear force device having a torque of 50 N·m or more.
[0018] The above-mentioned ordinary microcrystalline cellulose refers to a microcrystalline cellulose product whose average particle size D50 and / or loose density are different from those of the present invention. The average particle size D50 is more than 25 μm, and / or the loose density is 0.50 g / ml or less. For example, there can be mentioned a microcrystalline cellulose product prepared from a raw material for preparing microcrystalline cellulose in the prior art by a conventional method in the technical field, a microcrystalline cellulose filter cake or semi-finished product prepared from natural cellulose pulp subjected to a conventional hydrolysis method or electron beam irradiation method, or an existing commercially available microcrystalline cellulose product. As an example of the conventional hydrolysis method, cellulose pulp is acid hydrolyzed at a temperature of 110 to 170° C. and an acid concentration of 0.03 to 0.35 mol / L, washed, and filtered to obtain a filter cake. As an example of the electron beam irradiation method, microcrystalline cellulose is produced by electron beam irradiation at an irradiation dose of 0.2 Mrad to 10 Mrad. The raw material of the natural cellulose pulp is not particularly limited and may be any material commonly used in the art for the production of microcrystalline cellulose, including but not limited to the following raw materials or pulps: wood pulp, hemp pulp, bamboo pulp, cotton, cotton linters, straw, reed, straw pulp, cane bagasse, algae, bacterial microorganisms, etc. The existing commercially available microcrystalline cellulose products include, but are not limited to, microcrystalline cellulose products with code names such as PH101, PH102, PH112, PH301, PH302, PH105 or PH103.
[0019] wherein in the above process, the microcrystalline cellulose particles are obtained from material processed by a high shear device, which optionally further comprises steps of dilution, dispersion, drying, sieving and / or milling.
[0020] Another object of the present invention is to provide the use of said microcrystalline cellulose particles as an adjuvant or carrier in industries such as pharmaceutical, health food, food, industry, light industry, daily chemicals, petroleum, personal care, and agricultural chemicals.
[0021] The particles in the microcrystalline cellulose particles of the present invention can also be understood as powder, etc. They refer to microcrystalline cellulose products having granular or powdery particles with an average particle size D50 of 1 to 25 μm and a loose density of 0.50 to 0.80 g / ml.
[0022] The high shear device or equipment used in the present invention can reduce the particle size by applying extremely high shear force and mechanical actions such as pressure and friction. Unlike conventional methods for producing microcrystalline cellulose, the present invention does not use a solid grinding aid during high shear treatment, nor does it use a water-soluble grinding aid such as a salt, so that microcrystalline cellulose can be subjected to high shear treatment.
[0023] The high shear device or equipment of the present invention may be a continuous device or an intermittent device, and may be divided into a plurality of repeating steps for use. In general, when using a screw device such as an extruder or kneader, the torque is desirably 20 N·m or more. In the embodiment of the present invention, the torque is 50 N·m or more and is controlled between 50 and 150 N·m. In an actual extrusion operation, the torque fluctuates. It is low at the beginning and increases later. For example, it is about 50 N·m at first and later becomes 100 N·m or more. The microcrystalline cellulose product prepared by this method can reach the particle size and density described in the present invention.
[0024] In the high shear mechanical processing used in the present invention, the solid content of the material is generally 15%-60%, preferably 30%-50%. If the material to be processed is hydrolyzed microcrystalline cellulose filter cake and the solid content is too high, an appropriate amount of water can be added before or during processing until the appropriate solid content is achieved. If the solid content is too low, it can be dewatered before or during the high shear processing. The dewatering method can be centrifugation, filtration, pressing, infrared irradiation, hot blowing, air blowing, or a combination thereof. It can also be obtained by adding a high solid content of dried powder of microcrystalline cellulose or hydrolyzed microcrystalline cellulose filter cake to make the solid content of the final mixture appropriate. If the material to be processed is an existing microcrystalline cellulose powder, an appropriate amount of water can be added before or during processing until the appropriate solid content is achieved. The solid microcrystalline cellulose powder can be factory-produced microcrystalline cellulose powder or commercially available existing products, such as, but not limited to, PH101, PH102, PH112, PH301, PH302, PH105, PH103, etc.
[0025] Unlike conventional methods such as milling for preparing microcrystalline cellulose products, the method of the present invention significantly increases the density of microcrystalline cellulose while reducing the particle size by controlling the mechanical action of high shear force, thereby enabling the production of high-performance microcrystalline cellulose products with small particle size and high density.
[0026] In the present invention, the material treated by the high shear device can be further diluted and dispersed with an appropriate amount of water, and the general solid content during dispersion treatment can be controlled to 1% to 25%. The dispersion device used can be any high shear dispersion device such as a high shear mixer, a homogenizer, or a homogenizer pump, but is not limited thereto.
[0027] The diluted / dispersed material can be further dried by spray drying, fluidized bed drying, airflow drying, flash drying, etc. If necessary, the dried material can be further sieved and / or milled.
[0028] In the present invention, when the cellulose raw material or cellulose pulp is used to prepare the hydrolyzed microcrystalline cellulose filter cake, any pulp and source of the cellulose raw material can be applied, including but not limited to wood pulp, hemp pulp, bamboo pulp, cotton, cotton staple cashmere, straw, reed, straw pulp, sugarcane bagasse, algae, bacterial microorganisms, etc.
[0029] The ultrafine high-density microcrystalline cellulose product produced by the present invention can be applied to all known application fields of microcrystalline cellulose, and can also be applied to all potential or emerging application fields, including pharmaceuticals, health foods, industry, light industry, daily chemicals, petroleum, personal care, agrochemicals, etc. In the pharmaceutical field, its uses include, but are not limited to, binders, disintegrants, excipients, taste masking agents, dispersants, adsorbents, etc. The product of the present invention can be used in all formulation processes, including, but not limited to, wet granulation, dry granulation, direct compression, extrusion spheronization, spray drying, pellets, microtablets, coating, liquid formulations, creams, injections, sprays, etc. In addition, medicinal uses include herbal medicines, etc. The microcrystalline cellulose powder of the present invention can also be widely used in the food field. For example, it can be applied to various dairy products such as milk drinks, solid drinks, coffee / tea drinks, and carbonated drinks, meat products, jams, seasonings, soups, frozen foods, yogurt, fermented milk, cheese, biscuits, etc. In addition to these traditional food applications, the ultrafine crystalline cellulose of the present invention can also be applied in some new fields. For example, due to its unique and delicate taste and taste masking or taste adjusting function, ultrafine crystalline cellulose can be used as a carrier of flavor substances, pigments or other nutrients, especially in compressed candies. Its excellent function and flowability greatly improve the quality and performance of compressed candies. It can also reduce or replace the use of sugar alcohols. Further applications include, but are not limited to, its use as an encapsulating agent or excipient for active microorganisms in spray drying and tabletting.
[0030] The microcrystalline cellulose product of the present invention has a small particle size and a high loose density, which improves properties such as fluidity and compressibility, and the field of application is wide. In particular, the microcrystalline cellulose product of the present invention has a unique particle shape that is spherical or quasi-spherical particles. All existing microcrystalline cellulose products on the market are products with fibrous cross sections, and no spherical particles exist. Furthermore, the angle of repose of the microcrystalline cellulose of the present invention is smaller than that of UF-702, which has the smallest angle of repose among microcrystalline cellulose products currently on the market. The microcrystalline cellulose product of the present invention not only has properties that are very suitable for the tableting process, such as good fluidity and strong compressibility, but also has a small particle size and a spherical or nearly spherical shape, which makes it suitable for molding pharmaceuticals and foods, as it has a fine taste and texture and can mask odors.
[0031] BRIEF DESCRIPTION OF THE DRAWINGS Figure 1. Particle structure diagram of the product of Example 1 under a 32x optical microscope Figure 2. Particle structure diagram of the product of Example 1 taken with an optical microscope at 63x magnification Figure 3. Particle structure diagram of commercially available AVICEL PH101 taken with an optical microscope at 32x magnification [Mode for carrying out the invention] The following examples are intended to explain and illustrate the contents of the present invention, which should not be construed as limiting the protection scope of the present invention.
[0032] The particle size, density, angle of repose and microscope measurement in the present invention are as follows.
[0033] 1. Particle size distribution, measured with a Malvern 2000 laser particle size analyzer.
[0034] 2. How to measure loose density. Take microcrystalline cellulose powder and add it to a dry 100ml measuring cylinder up to the 100ml mark, and let the powder settle naturally. When the top is horizontal, read the powder volume v (ml). Pour out all the powder and weigh it in m (g). Loose density = m / v (g / ml).
[0035] 3. Method for measuring tap density: Place the measuring cylinder containing the loose density measurement material on a vibration meter and vibrate it 500 times to read the volume V (ml) and convert it into density m / v (g / ml).
[0036] 4. Method for measuring the angle of repose. Use the fixed cone method. Pour the microcrystalline cellulose powder through a funnel into the centre of a disk of a certain diameter. The radius of the disk is r. Stop pouring until the material on the hypotenuse of the powder bed flows automatically along the edge of the disk. Measure the height h of the cone formed by the powder accumulation. Calculate the angle of repose θ=arctan(h / r).
[0037] 5. Measurement by optical microscope. Take a small amount of microcrystalline cellulose powder on a slide glass, add a small amount of absolute ethanol to disperse it evenly, then place it under the microscope to observe, adjust the appropriate magnification and fine-tune to make the image clear.
[0038] In actual extrusion processing, the torque fluctuates. The torque is small at first. For example, it is about 50 N·m at first, then the torque increases and generally reaches 100-150 N·m. When the torque exceeds 150 N·m, the limit of the equipment is reached. When the torque is 100 N·m or more, the prepared microcrystalline cellulose products can reach the particle size and density described in the present invention.
[0039] Example 1 Cellulose pulp obtained from commercially available wood is collected and subjected to high-temperature acid hydrolysis (hydrolysis temperature 115-170°C, acid concentration 0.03-0.35 mol / L) for 1-2 hours to obtain hydrolyzed microcrystalline cellulose, which is then filtered and washed to a pH of 4-5 to increase the solid content in the cake to 40%. The solid filter cake is extruded three times in a high-shear extrusion device (a continuous extruder with a high-shear blade), with the torque of the extrusion device controlled to 50-150 N·m. Cooling water is introduced into the middle layer of the extruder for cooling. The extrudate is diluted with water, stirred, neutralized to a pH of 5-8, and then spray-dried to obtain the microcrystalline cellulose product of the present invention.
[0040] Through the measurement of particle size, density and angle of repose, the microcrystalline cellulose particle product obtained above has a loose density of 0.670g / ml and a tap density of 0.807g / ml. Its particle size distribution is D10 8.721μm, D50 19.776μm, D90 48.369μm. The angle of repose is 27.8°.
[0041] The microcrystalline cellulose particle product obtained above was observed under an optical microscope at 32x and 63x magnification, respectively. The results are shown in Figures 1 and 2. It can be seen that the product is spherical or quasi-spherical particles, and has a unique particle shape.
[0042] For comparison, let's take the most popular microcrystalline cellulose product on the market, AVICEL PH101, and observe its morphology under a 32x optical microscope. The results are shown in Figure 3, which shows the cross-sectional shape of the fibers.
[0043] Example 2 Commercially available Vivapur PH102 microcrystalline cellulose powder is used, whose ultimate degree of polymerization is 225. Through particle size and density measurement, the loose density is 0.32g / ml, the tapped density is 0.44g / ml, the particle size distribution D10 is 29.623μm, D50 is 104.997μm, and D90 is 227.668μm.
[0044] Weigh out 500 g of Vivapur PH102 microcrystalline cellulose powder, add 500 g of water, and mix to a solid content of 50%. The filter cake of this solid content is extruded three times in a high shear extruder, and the torque of the extruder is controlled between 50 and 150 N·m. In the middle layer of the extruder, it is cooled by cooling water. The extrudate is diluted with water, stirred, neutralized to pH 5 to 8, and then spray-dried to obtain the microcrystalline cellulose product of the present invention.
[0045] Through the measurement of particle size and density, the microcrystalline cellulose product obtained above has a loose density of 0.598g / ml, a tap density of 0.738g / ml, a particle size distribution D10 of 8.629μm, a D50 of 18.649μm and a D90 of 36.61μm.
[0046] Example 3 Cellulose pulp obtained from commercially available bamboo is collected and acid-decomposed at high temperature (hydrolysis temperature 115-170°C, acid concentration 0.03-0.35 mol / L) for 1-2 hours to obtain hydrolyzed microcrystalline cellulose, which is then filtered and washed with water until the pH is 4-5. The filter cake is diluted with water and neutralized to pH 5-8, and then spray-dried to obtain conventional microcrystalline cellulose products. Measurements were performed on the obtained microcrystalline cellulose powder, revealing that the loose density was 0.440 g / ml, the tap density was 0.575 g / ml, and the particle size distribution D50 was 39.01 μm.
[0047] The bamboo pulp microcrystalline cellulose filter cake obtained above is controlled to a solid content of 40%, extruded three times with a high shear extrusion device, and the torque of the extrusion device is controlled to 50-150 N·m to obtain bamboo pulp microcrystalline cellulose. Cooling water is introduced into the middle layer of the extruder for cooling. The extrudate is diluted with water, stirred, neutralized to pH 5-8, and then spray-dried to obtain the microcrystalline cellulose product of the present invention.
[0048] Through the measurement of particle size and density, the microcrystalline cellulose product prepared above has a loose density of 0.624g / ml, a tap density of 0.811g / ml, and particle size distribution of D10 of 5.613μm, D50 of 12.221μm and D90 of 31.201μm.
[0049] Example 4 Cellulose pulp obtained from commercially available hemp fiber is collected and subjected to high-temperature acid hydrolysis (hydrolysis temperature 115-170°C, acid concentration 0.03-0.35mol / L) for 1-2 hours to obtain hydrolyzed microcrystalline cellulose. It is washed with water to pH 4-5, and the filter cake is diluted with water and neutralized to pH 5-8, and then spray-dried to obtain conventional microcrystalline cellulose products. The obtained microcrystalline cellulose powder was quantified, and the loose density was 0.388g / ml, the tap density was 0.561g / ml, and the particle size distribution D50 was 36.7μm.
[0050] The hemp pulp microcrystalline cellulose filter cake obtained above was controlled to a solid content of 40%, extruded three times with a high shear extrusion device, and extruded with an extruder while controlling the torque of the extrusion device to be 50 to 150 N·m. Cooling water was passed through the middle layer of the extruder to cool it. The extrudate was diluted with water, stirred, neutralized to pH 5 to 8, and then spray-dried to obtain the microcrystalline cellulose product of the present invention.
[0051] The particle size and density measurements of the above prepared microcrystalline cellulose product showed a loose density of 0.619 g / ml, tapped density of 0.774 g / ml, particle size distribution of D10 of 6.665 μm, D50 of 14.447 μm, and D90 of 30.297 μm.
[0052] Example 5 Cellulose pulp obtained from commercially available wood is collected and acid hydrolyzed at high temperature (hydrolysis temperature 115-170°C, acid concentration 0.03-0.35 mol / L) for 1-2 hours to obtain hydrolyzed microcrystalline cellulose, which is then filtered and washed to adjust the pH to 4-5 and increase the solid content in the cake to 42%. The solid filter cake is extruded three times in a high shear extrusion device (a continuous extruder with a high shear blade), and the torque of the extrusion device is controlled to 50-150 N·m. Cooling water is introduced into the middle layer of the extruder for cooling. The extrudate is diluted with water, stirred, neutralized to pH 5-8, and then spray-dried to obtain the microcrystalline cellulose product of the present invention.
[0053] The particle size, density and angle of repose of the microcrystalline cellulose particles obtained above were measured, and the loose density was 0.600 g / ml, the tapped density was 0.730 g / ml, the particle size distribution was D10 8.773 μm, D50 21.459 μm, D90 48.528 μm, and the angle of repose was 30.5°.
[0054] Comparative Example Cellulose pulp obtained from commercially available wood is collected and acid-hydrolyzed at high temperature (hydrolysis temperature 115-170°C, acid concentration 0.03-0.35 mol / L) for 1-2 hours to obtain hydrolyzed microcrystalline cellulose, which is then filtered and washed to increase the pH to 4-5 and the cake solid content to 35%. This solid filter cake is extruded three times using a high-shear extrusion device (continuous extruder with high-shear blade), and the torque of the extrusion device is controlled to 14-20 N·m during the extrusion process. Note that the torque gradually increases as water evaporates during the extrusion process, and can be suppressed to 20 N·m or less by adding an appropriate amount of water. Cooling water is introduced into the middle layer of the extruder for cooling. The extrudate is diluted with water, stirred, neutralized to pH 5-8, and then spray-dried to obtain the microcrystalline cellulose product of the present invention.
[0055] Measurements of particle size and density showed that the resulting microcrystalline cellulose particles had a loose density of 0.487 g / ml, a tap density of 0.574 g / ml, and a particle size distribution D10 of 11.598 μm, D50 of 37.001 μm, and D90 of 87.476 μm. [Brief description of the drawings]
[0056] [Figure 1] Particle structure diagram of the product of Example 1 under a 32x optical microscope [Diagram 2] Particle structure diagram of the product of Example 1 taken with an optical microscope at 63x magnification [Diagram 3] Particle structure diagram of commercially available AVICEL PH101 taken with a 32x optical microscope
Claims
[Claim 1] Microcrystalline cellulose particles characterized in that the average particle size D50 is 1 to 25 μm and the loose density is 0.50 to 0.80 g / ml.
Citation Information
Patent Citations
Cosmetic base
JP1980027126A
Microcrystalline cellulose product and method of making same
JP1995507692A